Galanin neurons in the ventrolateral preoptic area promote sleep and heat loss in mice. Issue 1 (December 2018) - Kroeger, Daniel; Absi, Gianna; Gagliardi, Celia; Bandaru, Sathyajit; Madara, Joseph; Ferrari, Loris; Arrigoni, Elda; Münzberg, Heike; Scammell, Thomas; Saper, Clifford; Vetrivelan, Ramalingam
Abstract The preoptic area (POA) is necessary for sleep, but the fundamental POA circuits have remained elusive. Previous studies showed that galanin (GAL)- and GABA-producing neurons in the ventrolateral preoptic nucleus (VLPO) express cFos after periods of increased sleep and innervate key wake-promoting regions. Although lesions in this region can produce insomnia, high frequency photostimulation of the POAGAL neurons was shown to paradoxically cause waking, not sleep. Here we report that photostimulation of VLPOGAL neurons in mice promotes sleep with low frequency stimulation (1–4 Hz), but causes conduction block and waking at frequencies above 8 Hz. Further, optogenetic inhibition reduces sleep. Chemogenetic activation of VLPOGAL neurons confirms the increase in sleep, and also reduces body temperature. In addition, chemogenetic activation of VLPOGAL neurons induces short-latency sleep in an animal model of insomnia. Collectively, these findings establish a causal role of VLPOGAL neurons in both sleep induction and heat loss. Anatomical lesions of the preoptic area (POA) can cause sleep loss while electrical, chemical, or thermal stimulation of POA can induce sleep. To better understand the exact neural function of the POA, this study shows that galanin and GABA+ inhibitory neurons in the ventrolateral POA that project to the wake-promoting tuberomammillary nucleus promote sleep in a stimulation frequency dependent manner.